BOUNDING MIDDLE PERIOD CEMETERY USE IN SAN PEDRO DE ATACAMA, CHILE. Issue 1 (3rd February 2021) - Pestle, William J; Torres-Rouff, Christina; Pimentel, Gonzalo; Hubbe, Mark
ABSTRACT: The San Pedro de Atacama oases, located in northern Chile's hyperarid Atacama Desert, have been occupied for at least 3000 years. Here, we examine cemetery use in the oases, with emphasis on the Middle Period (ca. AD 400–1000). By modeling of a large corpus (n=243) of radiocarbon dates, over 90% of which are direct AMS assays of human bone collagen, we attempt to establish a temporal framework by which to explore the establishment of formalized social inequality in this period. Modeling of these dates at three locally defined scales (all ayllus, inter- ayllu, and intra- ayllu ) permit heretofore unavailable insights into the chronological and spatial dimensions of life and mortuary activity in the oases and allow us to better contextualize patterns of social inequality during the dynamic Middle Period. The results of this modeling indicate two distinct peaks of occupation during the Middle Period in San Pedro and document significant temporal variability in cemetery use patterns on both inter- and intra- ayllu scales. These results stress the importance of local social and environmental factors to the occupation of the oases and provide crucial chronological structure for future archaeological and bioarchaeological research in the region.